The Diagnostic Apathia Scale predicts the ability to return to work following depression or anxiety. Issue 6 (25th September 2013) - Hellström, LC; Eplov, LF; Nordentoft, M; Østergaard, SD; Bech, P
<x content-type="archive" xml:space="preserve">Abstract</x> Objective The aim of this study was to evaluate the validity of a new apathy rating scale in predicting the ability to return to work (RTW) in patients with depression or anxiety a year after discharge from a psychiatric hospital. Methods We evaluated 56 patients with depression or anxiety, who participated in an on-going randomised clinical trial using RTW as primary outcome. The degree of apathy was measured by the Diagnostic Apathia Scale, which contains six items covering the following neuropsychological symptoms: concentration/memory problems, difficulties in decision making, lassitude, tiredness/fatigue, insomnia, and reduced ability to work and engage in personal interests. The scale was analysed for psychometric validity (scalability) and for its ability to predict RTW. Finally, the predictive validity of the Diagnostic Apathia Scale regarding RTW was compared with scales measuring severity of depression/anxiety symptoms, disability, and psychological well-being. Results The Diagnostic Apathia Scale displayed sufficient scalability, that is, the total score was a psychometrically valid measure of apathy. Only the Diagnostic Apathia Scale, and not the scales measuring severity of symptoms, disability, or psychological well-being, had predictive validity regarding RTW. Thus, 76% with 'clinically significant apathy' at baseline were unable to RTW versus 50% of the patients without apathy (p<0.05). Conclusion The Diagnostic Apathia Scale was found to have an acceptable predictive validity in terms of patients' ability to RTW 1 year after discharge from hospitalisation for depression or anxiety.